Monitoring well pattern deployment in China gas storage and its initial success rate. (December 2020) - Ligen, Tang; Weiyao, Zhu; Huayin, Zhu; Yan, Wang; Huaquan, Jiang; Ping, Peng; Deshu, Li; Jieming, Wang; Chun, Li; Ying, Yang; Ke, Ren; Zhide, Wu; et al.
Highlights: We add one element (legacy well facilities) to modify traditional trap in the domain of gas storage. We evaluate the leakage risk of gas reservoir traps through faults, wells, and caprock. We establish the sequence of gas accumulation after leakage, which is much useful than leakage evaluation. We drill five new wells to separately monitor five overlying layers. We find no conclusive evidence of gas leakage from storage to upper layers. Abstract: The present study assessed the possibility of a gas leak from a gas storage area by using modified reservoir trap and then deployed monitoring wells in accordance with the accumulation sequence after a gas leak. Using the previous history of reservoir exploration and development techniques, we used conventional trap elements such as reservoir rocks, capping rocks, and faults, as well as well facilities to delineate an new trap in underground gas storage area. Due to inter-layer differential pressure, gas may leak along capping beds, faults, and well facilities, thus first accumulate in P1 q (1st overlying permeable layer), then in P1 m (2nd overlying permeable layer), P2 ch (3rd overlying permeable layer), and finally in shallower zones. According to the sequence of gas accumulation, we deployed five monitoring wells to separately monitor four overlying layers and storage layer. We detected the abnormal pressure mainly in P1 m and then excluded the possibility of an abnormal pressure change caused by a gas leak. The monitoring results within the underground gas storage and the monitoring well pattern were useful and satisfactory. We presented the first example of a deployment of a monitoring well pattern for an underground gas storage area, which may provide technical support to the construction of new gas storage areas and geological sequestration of CO2 .